Changing Healthcare Providers’ Behavior during Pediatric Inductions with an Empirically-based Intervention - Martin, Sarah R. (2011)
BACKGROUND: Each year over 4 million children experience significant levels of preoperative anxiety, which has been linked to poor recovery outcomes. Healthcare providers (HCP) and parents represent key resources for children to help them manage their preoperative anxiety. The present study reports on the development and preliminary feasibility testing of a new intervention designed to change HCP and parent perioperative behaviors that have been previously reported to be associated with children’s coping and stress behaviors before surgery. METHODS: An empirically-derived intervention, Provider-Tailored Intervention for Perioperative Stress, was developed to train HCPs to increase behaviors that promote children’s coping and decrease behaviors that may exacerbate children’s distress. Rates of HCP behaviors were coded and compared between pre-intervention and post-intervention. Additionally, rates of parents’ behaviors were compared between those that interacted with HCPs before training to those interacting with HCPs post-intervention. RESULTS: Effect sizes indicated that HCPs that underwent training demonstrated increases in rates of desired behaviors (range: 0.22 to 1.49) and decreases in rates of undesired behaviors (range: 0.15 to 2.15). Additionally, parents, who were indirectly trained, also demonstrated changes to their rates of desired (range: 0.30 to 0.60) and undesired behaviors (range: 0.16 to 0.61). CONCLUSIONS: The intervention successfully modified HCP and parent behaviors. It represents a potentially new clinical way to decrease anxiety in children. A recently National Institute of Child Health and Development funded multi-site randomized control trial will examine the efficacy of this intervention in reducing children’s preoperative anxiety and improving children’s postoperative recovery is about to start.